WORKSHOP AL-QUR'AN: PEMAHAMAN DAN APLIKASI TATA CARA PEMBACAAN YANG BENAR BAGI MAHASISWA - Samsuri; Warto; Rendi Nugraha; Estia Dwi Andini (Jurnal Istimā, 2025)
The low ability to read the Qur'an properly and correctly is still a common problem among students, especially related to the mastery of tahsin, tajweed, and makharijul letters. This condition shows the need for a systematic training program to improve the quality of Qur'an reading. This workshop aims to equip students with a comprehensive understanding of the rules of tahsin and train their ability to apply the procedures for reading the Qur'an according to the correct standards. The workshop was carried out through a theoretical and practical approach with classical methods, qiroah, and talaqqi exercises, involving 65 students of the Sharia Banking Study Program FAI UMT on May 1-30, 2025. The results of the activity showed a significant increase, where most of the participants were able to read the Qur'an more eloquently and according to the rules of tahsin. This activity is also the basis for evaluating and strengthening the curriculum to improve students' Qur'an reading competence in the future.